2003
DOI: 10.1002/jbm.a.10162
|View full text |Cite
|
Sign up to set email alerts
|

The effect of silica‐containing calcium‐phosphate particles on human osteoblasts in vitro

Abstract: There is an ongoing need for more effective and less costly bone substitutes. It has previously been proposed that silica-containing bioactive glass would be more effective as a bone repair material because of its physiochemical properties. Three newly synthesized silica-containing bioactive glass formulations, HA-31 (25%), HA-11 (50%), and HA-13 (75%), were tested as biocompatible substrates for the continued proliferation and phenotype expression of human bone cells in vitro. Two currently available bioactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 30 publications
3
35
0
3
Order By: Relevance
“…Silica containing calcium phosphate have shown osteoinductivity in human osteoblast cultures in vitro 15 and preparations with various silica and calcium phosphate compositions are under clinical studies 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Silica containing calcium phosphate have shown osteoinductivity in human osteoblast cultures in vitro 15 and preparations with various silica and calcium phosphate compositions are under clinical studies 16 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, pore distribution, interconnectivity and size are of paramount significance in order to assurance of proper cell proliferation and migration, as well as tissue vascularization and diffusion of nutrients. The concept of using bioactive glass substrates as templates for in vitro synthesis of bone tissue for transplantation by assessing the osteogenic potential has been investigated (Xynos et al, 2000;Phan et al, 2003;Chen et al, 2008;Brown et al, 2008) and confirmed that Bioglass scaffolds have potential as osteoconductive tissue engineering substrates for maintenance and normal functioning of bone tissue ). Human primary osteoblast-like cells cultured in contact with different bioactive glass suggested that bioglass not only induces osteogenic differentiation of human primary osteoblast-like cells, but can also increase collagen synthesis and release.…”
Section: Bioactive Glasses' In Biomolecular Engineering With Special mentioning
confidence: 94%
“…4,[6][7][8] Emellett a kalcium-foszfát tartalmú szilikagél humán in vitro osteoblast sejtkultúrákon mutatott oszteoinduktivitást. 5,9 Ezeken felül olyan tulajdonságaik is szerephez juthatnak, melyeket eddig még nem sikerült teljesen kiaknázni. A vizsgált minták elő-állítási technológiája lehetővé teszi az anyagban lévő pórusok méretének, ezzel együtt az átjárhatóságnak széles tartományban történő beállítását.…”
Section: Anyagokunclassified
“…A jelölésre alkalmazott, kristályrácsba beépített európium-foszfátot nanokristályos formában az irodalomban már használták sejtek nyomjelzésére, nem volt toxikus, így nem vártunk különösebb reakciót. [9][10][11] A primer kísérleti nyomószilárd-sága 118 MPa, porozitása nagyobb, mint a későbbiekben említendő GY3-é.…”
Section: Eredeti Közleményekunclassified